A trait space at an overarching scale yields more conclusive macroecological patterns of functional diversity - Múrria, Cesc; Iturrarte, Gabone; Gutiérrez‐Cánovas, Cayetano; Baselga, Andres (Global ecology and biogeography, 2020)
Aim Macroecological studies have commonly used study‐specific subsets of taxa to calculate metrics of functional diversity (FD) and explore their spatial patterns. However, FD metrics can be biased if the functional space (FS) does not cover an extensive, common and representative range of trait variation. Here, we propose an overarching FS covering the widest range of European freshwater taxa and trait variation compiled to date for a better evaluation of macroecological FD patterns. Location Six regions distributed from Morocco to Scandinavia. Time period 2008. Major taxa studied Major orders of European freshwater macroinvertebrates (541 taxa). Methods FD metrics (functional richness, dispersion and evenness) were estimated on FSs covering three decreasing grain sizes of trait variation: an overarching European scale (541 taxa), a continental context‐dependent scale that covers six regions (180 taxa) and six regional scale FSs (63–108 taxa). Taxonomic richness and FD metrics were modelled over the latitudinal gradient. Null models were performed to assess if FD patterns were independent of taxonomic richness variation and to identify community assembly mechanisms (filtering or overdispersion) along the latitudinal gradient. Results The scale at which FSs were calculated influenced the shape and strength of the latitudinal FD patterns. Continental or regional scale FSs captured different axes of trait variation associated with scale‐specific taxa composition. These FS axes and resulting FD metrics moderately or poorly represent those based on the overarching FS. Null model analysis revealed distinct latitudinal patterns for each FS and FD metric, which led to contrasting assembly mechanisms along latitude. Main conclusions An overarching FS (a) captures a wide, common and more representative range of trait variation, (b) offers a more generalizable framework to explore large‐scale functional patterns and community assembly mechanisms, and (c) enhances the comparison of FD metrics across studies to obtain more reliable macroecological patterns.